ACCOUNTING AND ECONOMICS. - Heilman, E. A. (The Accounting Review, 1935)
The relation of accounting to economics has been the subject of discussion a number of times, but no program devoted to accounting relationships would seem complete without some expression on the subject of economics. The economist and the accountant have been members of the same family for a number of decades, since the early period in which economics permitted this fledgling to enter the liberal arts colleges under the shadow of its protecting wing. They later became chief partners with business law in the organization of curricula in business and schools of business. However, there are many indications that the two fields are coming closer to a mutual understanding. Economics is developing most rapidly in the field of statistics and statistical method and in this type of study is reaching more and more into fields hither-to largely the habitat of the accountant. Also, finance and marketing, among others, are studying problems closely connected with accounting and in which the accountant is apt to contribute much of the useful material.